2000
DOI: 10.1016/s0735-1097(00)00985-2
|View full text |Cite
|
Sign up to set email alerts
|

The incremental prognostic importance of body fat adjusted peak oxygen consumption in chronic heart failure

Abstract: The adjustment of PkVO2 to lean body mass increases the prognostic value of cardiopulmonary stress testing in the evaluation of patients with chronic heart failure. The use of <19 ml O2/kg of lean body mass/min as a cutoff in PkVO2 should be used for timing transplantation, particularly in women and the obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 19 publications
5
100
0
4
Order By: Relevance
“…21 Estimating fitness, independent from obesity, has been shown to improve the accuracy of fitness as a predictor of cardiac function. 22 Further studies are necessary to show whether dividing VO 2max by fat-free mass, rather than by total body mass, can avoid the bias against obese individuals that is illustrated in our results. To our knowledge, this is the largest population-based sample with objectively measured VO 2max and glucose tolerance in the literature.…”
Section: Discussionmentioning
confidence: 83%
“…21 Estimating fitness, independent from obesity, has been shown to improve the accuracy of fitness as a predictor of cardiac function. 22 Further studies are necessary to show whether dividing VO 2max by fat-free mass, rather than by total body mass, can avoid the bias against obese individuals that is illustrated in our results. To our knowledge, this is the largest population-based sample with objectively measured VO 2max and glucose tolerance in the literature.…”
Section: Discussionmentioning
confidence: 83%
“…[13][14][15] In addition, CPX may lose prognostic power in certain subgroups with high percentage of body fat, such as women and obese patients, especially in the era of β-blockers. 13,[15][16][17] We have demonstrated that adjusted exercise indices (including peak VO 2 and peak O 2 pulse) all predict prognosis better than nonadjusted indices ( Figure 1 and Figure 2). 16,17 This information may be particularly applicable to the favorable prognosis in obese patients with HF and women with higher levels of body fat.…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 88%
“…[12][13][14][15] However, this parameter is generally corrected for total weight (as opposed to lean weight), despite the fact that fat is not aerobically active. 13,[15][16][17] We present a case to illustrate important concepts regarding the obesity paradox.…”
Section: Mandeep R Mehra Md; Hector O Ventura MD Editorsmentioning
confidence: 99%
See 2 more Smart Citations